Diseño de una máquina precortadora y selladora de rollos de película plástica para la formación de bolsas para la empresa Plásticos la Hogareña Bustos Y Cia S En C. (2018)
The present project was carried out to obtain a machine that would allow the sealing and precutting of the plastic film roll produced by the extruder in the company Plásticos la Hogareña Bustos y Cia S en C. Currently the company is doing this process separately by two machines, which generates an increase in production time. At the same time, it has a precutting machine which is in poor condition since the maintenance that is applied is minimal and clearly corrective. The project aimed at the design of a machine that allows to carry out the pre-cutting and sealing process, for the replacement of existing machines. The machine must allow the variation of the dimensions of the bags, in three fixed sizes that are 20x40 cm, 45x60 cm and 70x80 cm and with the least possible loss of material by this action, the expected production is 18 rolls of plastic film precut and sealed in 9-hour shifts.